Metabolic syndrome and diabetes mellitus in Mexico: the role of PET/CT in endothelial dysfunction and cardiovascular disease detection (2017)
Purpose of Review Metabolic syndrome (MetS) and diabetes mellitus (DM) have become over the past years a global burden of disease. They are one of the main risk factors for cardiovascular disease among others. CVDs represent the number one cause of death globally. Diabetes Mellitus’ prevalence, especially type 2, has increased dramatically in a short period increasing health care costs and mortality worldwide. Detecting coronary artery disease in diabetic patients with a myocardial perfusion imaging method such as PET/CT is the primary concern for this review. Recent Findings The most recent survey in Mexico done in 2012 reveals that an overall prevalence of 9.4% of the population has DM, which is roughly 6.4 million people with DM. Myocardial perfusion imaging with PET/CT has proven to be an accurate method to assess myocardial perfusion defects and viability in both symptomatic and asymptomatic patients with DM. Summary In this review, we briefly describe the latest data on DM in Mexico and the use of MPI with PET/CT for patients with this disease, creating a discussion of the use of this technique as a screening method for endothelial dysfunction to prevent cardiovascular outcomes.